Light induced degradation: kinetic model and grain boundary impact on sponge-LID. (September 2017) - Sporleder, Kai; Hübener, Kati; Petter, Kai; Kranert, Christian; Luka, Tabea; Turek, Marko
Abstract: High-performance multi-crystalline silicon material (HPmc-Si) dominates the market for casted p-type silicon. Solar cells made from HPmc-Si material might suffer from light induced degradation due to the so called sponge-LID mechanism. In this work, we present a kinetic sponge-LID model showing that the degradation follows a pairing reaction involving two reactants. This implies that sponge-LID is based on a different reaction scheme compared to the well-known models for boron-oxygen- or iron-boron-degradation. Based on our model, degradation rates are investigated reading the influence of temperature and illumination on the degradation. Finally, we present statistical results implying that Sigma-3 grain boundaries are less affected of the degradation than other grain boundary types. Using a detailed spatially resolved analysis of the effective carrier diffusion length, the different behaviour of grain boundaries and intra-grain regions is quantified.